The challenges of a biodiesel implementation program in Malaysia - Zulqarnain, (MDPI AG, 2020)
The palm biodiesel industry is facing many challenges implementing biodiesel program in Malaysia. This paper addresses the importance of the B10 blend (10 biodiesel, 90 petroleum diesel), global challenges of palm oil import and export, and protective measures for continuous positive growth of the palm oil sector. Palm oil is the backbone of Malaysiaâs economy, covering more than 5 of its gross domestic product (GDP). The key steps taken by the Malaysian government for the successful implementation of the B10 program are discussed in this review study. Till now, B5 and B7 biodiesel programs have been successfully implemented in Malaysia. The B10 biodiesel program is attractive because of the developed local palm oil sector. The B10 biodiesel program will increase the use of renewable energy sources, and is expected to increase the productivity of palm oil and biodiesel implementation in the country. Despite successful B5 and B7 programs, Malaysia is facing challenges for the implementation of biodiesel due to fluctuation in crude palm oil prices, low domestic usage of palm oil, and vehicle warranty. The improvement of palm oil and promotion of B10 through targeted agencies in the central region of Malaysia will help to implement the biodiesel program successfully. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.